2021
DOI: 10.5115/acb.20.217
|View full text |Cite
|
Sign up to set email alerts
|

Fabella and patella variants: radiographic prevalence, distribution and clinical relevance in a population of black african descent

Abstract: To evaluate the radiographic characteristics and prevalence of fabella and patella variants in an indigenous African population. This retrospective observational study of orthogonal knee radiographs of 377 consecutive subjects was conducted in Lagos, Nigeria, from February 2017 to November 2017. The presence of bipartite/multipartite patella, as well as the presence of fabella were noted. The craniocaudal diameter, anteroposterior diameter, fabello-femoral distance and fabello-tibial distance of the fabella we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…In contrast, another Southeast Asian study from Singapore reported a lower incidence rate (31.25%) (17). Our findings were comparable to the lowest prevalence rates in South Africa (11.94%) and Nepal (12.3%) (18,19).…”
Section: Discussionsupporting
confidence: 69%
“…In contrast, another Southeast Asian study from Singapore reported a lower incidence rate (31.25%) (17). Our findings were comparable to the lowest prevalence rates in South Africa (11.94%) and Nepal (12.3%) (18,19).…”
Section: Discussionsupporting
confidence: 69%
“…Moreover, fabellae resemble loose bone fragments or osteophytes. The two most prominent methods for establishing a diagnosis accurately were USG and electromyography (Adedigba et al, 2021; Al Matroushi et al, 2021; Dale et al, 2018; Dalip et al, 2018; Takebe & Hirohata, 1981).…”
Section: Discussionmentioning
confidence: 99%
“…The typical shape of a fabella is circular or elliptical and it measures from 5 to 24 mm, although the biggest fabella described was 30 × 16 × 8 mm (Agathangelidis et al, 2016). Some studies report that fabellae are larger in males, but others find no significant difference (Adedigba et al, 2021; Akkoc et al, 2022; Al Matroushi et al, 2021; Dalip et al, 2018; Kawashima et al, 2007). The bilateral to unilateral fabella ratio is 2:1 or 3:1 according to most studies, with no sex differences (Hauser et al, 2015; Zeng et al, 2012).…”
Section: Anatomy Of the Fabellamentioning
confidence: 99%
See 1 more Smart Citation
“…It is detected more frequently in men and is bilateral with a rate of 43%. It may cause anterior knee pain, especially after trauma, sports injury, or overuse [ 1 , 2 ]. Treatment is primarily conservative in symptomatic cases, and surgery may be preferred in cases unresponsive to conservative treatment [ 3 ].…”
Section: Introductionmentioning
confidence: 99%